Production of singlet dominated scalar(s) at the LHC - Subhadip Bisal; Debottam Das; Swapan Majhi; Subhadip Mitra (Physics Letters B, 2023)
The leading order production of an SM singlet-like scalar has primarily been realized through the gluon fusion process by mixing with the SU(2)L scalar doublet of the model. The dominant part of the physical state, i.e., the singlet component, does not have any role in its direct production. Focusing on such a state with a mass smaller than the SM-like Higgs scalar, we calculate the dominant next-to-leading (NLO) order corrections to its production cross-section. With these improved cross-sections, the present and future LHC limits may become somewhat more stringent.